Experiences of Korean mothers of children with cancer: A Photovoice study. Issue 2 (4th March 2017) - Kim, Min Ah; Yi, Jaehee; Sang, Jina; Kim, Soo Hyun; Heo, InYoung
ABSTRACT: Using Photovoice, a participatory action research methodology, we investigated Korean mothers' lives postdiagnosis of their child with cancer. Photovoice was used to understand the mothers' perceptions of how they have adapted to their children's illnesses. Five mothers of children with cancer participated in five sessions of the Photovoice project, during which they took and shared photographs and narratives about their experiences and joined weekly group discussions on their selected themes. The following themes and subthemes emerged: "What I would like to do (taking a break, socializing with friends, spending time with other family members, developing my career), " "My child and food (whatever my child wants to eat, love of family), " "My days for my child (doing what my child wants to do, being a playmate, changing for my child), " and "Power sources for me (family, courage of children, mom is strong, hope)." Having a child with cancer greatly affects the mother's social and work lives as well as emotional well-being. Services and programs such as respite care, parenting education, and psychological support are recommended based on the study findings.